Peningkatan Hasil Belajar Mata Pelajaran Fikih Materi Thaharah Dengan Metode Al Tathbiq Di MTsN 6 Tabalong - Muhammad Yusran; Hardiansyah Hardiansyah; Hasan Hasan (STIT Syekh Muhammad Nafis Tabalong, 2025)
Problems with the learning outcomes of class VII motivate this research. The research focuses on a student who is performing at a standard level, highlighting their lack of mastery of the material. This research aims to determine whether there is an improvement in the learning outcomes of class VII. In the 2024/2025 academic year, a student at MTsN 6 Tabalong studied the Thaharah material using the al-tathbiq method. This research is a Classroom Action Research (CAR) conducted in 2 learning cycles. The research subjects were class VII. The study involved 30 students from class VII at MTsN 6 Tabalong. We collected data for this research through observation, tests, and documentation. The results of the observations and tests will be analyzed to determine the effectiveness of the al-tathbiq method in enhancing students' understanding of thaharah. By comparing pre- and post-test scores, the study aims to provide insights into the method's impact on student engagement and knowledge retention. The research results showed an increase from the pre-cycle to cycle I and cycle II. The pre-cycle results showed that 12 students completed the fiqh learning on the thaharah material, with a percentage of 38%. In cycle I, 16 students completed it, representing a 51% completion rate. Meanwhile, in cycle II, all 30 students completed it, with a percentage of 100%.